Business Communication Online Lecture Activities During the Covid-19 Pandemic of the Business Administration Study Program, Semarang State Polytechnic - Umar - Farouk; Nur - Rini; Erika - Devie; Paniya - Paniya; Irawan - Malebra (Admisi dan Bisnis, 2023)
The spread of the Covid-19 pandemic virus throughout the world has forced the world of education to carry out online education. Following the Community Activity Restriction (CAR) policy, Semarang State Polytechnic held online lecturing for all subjects. The purpose of this research is to evaluate online Business Communication lecturing activities to enable its improvement in the future.. This Classroom Action Research is a participatory empirical with students majoring in Business Administration, Semester 3, Academic Year 2021-2022. Data was collected by means of questionnaires, observations (field notes), library documents and other related documents, as well as complaints, appreciations and suggestions given by respondents. Descriptive analysis is done partially and integrally. The results of the study indicate that the biggest problem in online lecturing activities is that the electronic facilities used are not yet supported. Teaching factors, teaching methods, and administrative systems  supported the implementation of lectures whereas factors of student, facility and environment still need to be relatively improved